Application of the Open Cycle Stirling Engine Driven with Liquid Nitrogen for the Non-Polluting Automobiles - M.B. Kravchenko (Holodilʹnaâ Tehnika i Tehnologiâ, 2017)
Progress on advancing technology of using liquid nitrogen for the non-polluting automobiles is reported. It is shown that the low exergy efficiency of the known engines fueled with liquid nitrogen has discredited the very idea of a cryomobile. The design of the open-cycle cryogenic Stirling engine is proposed. This engine allows extracting up to 57% of the exergy accumulated in liquid nitrogen. The method used to calculate of such open-cycle Stirling engine is described and the calculation results and discussion are presented. It is shown that 200 liters of liquid nitrogen is sufficient for 180 km range of cryomobile at speed of 55 km/h, while a full charge of the 300-kilogram battery of Nissan LEAF electric vehicle is sufficient for a range of 160 km. Use of liquid nitrogen or liquid air as an energy vector in a transport will not require scarce materials, and, in comparison with using of lithium-ion batteries or hydrogen, this will require less capital investment.